Long‐term cognitive outcomes after cerebral sinovenous thrombosis in childhood. (9th September 2020) - Slim, Mahmoud; Aziz, Aly Shah; Westmacott, Robyn; Dlamini, Nomazulu; Deveber, Gabrielle; MacGregor, Daune; Yau, Ivanna; Andres, Kathleen; Moharir, Mahendranath
Abstract : Aim: To assess long‐term cognitive function in children after cerebral sinovenous thrombosis (CSVT). Method: Children with CSVT, who had neuropsychological testing for intellectual ability, executive function, attention, language, or behavior, were included in a prospective observational study. Outcomes were compared with normative means using one‐sample t ‐tests. Predictors of abnormal function were examined using logistic regression. Results: Fifty children with CSVT were included (median age at diagnosis 2y 10mo, interquartile range 7d–6y 10mo; 35 males, 15 females). The median follow‐up time was 4 years 2 months (interquartile range 2y 8mo–6y 4mo). Compared with normative means, children with CSVT had lower mean (± standard deviation) full‐scale IQ, working memory, and processing speed scores (93.3±16, p= 0.01; 93.6±16, p= 0.04; 93.7±15.3, p= 0.02 respectively). They also had lower scores in executive function, attention, and language domains. Refractory seizure at presentation was associated with a trend in behavioral problems (odds ratio [OR] 6.3, 95% confidence interval [CI] 0.9–46, p= 0.07). Females were less likely to experience processing speed difficulties (OR 0.22, 95% CI 0.04–1.3, p= 0.09). Incomplete recanalization was associated with a greater risk of abnormal verbal comprehension (OR 5.3, 95% CI 0.93–30.5, p= 0.059). Interpretation: Children with CSVT as a group performed below age expectations on standardized neuropsychological tests, although there was variability across individuals and cognitive domains. Larger studies are needed to evaluate predictors of cognitive deficits in children with CSVT.